Modulation of the kappa and mu opioid axis for the treatment of chronic pruritus: A review of basic science and clinical implicationsCapsule Summary - Sarina Elmariah, MD, PhD; Sarah Chisolm, MD; Thomas Sciascia, MD; Shawn G. Kwatra, MD (Elsevier, 2022)
Introduction: Treating chronic pruritus is challenging for dermatologists due to the lack of therapeutic options. We review the effects of κ-opioid receptor (KOR) and μ-opioid receptor (MOR) in the modulation of itch, summarize evidence supporting the efficacy and safety of opioid receptor-targeting agents in chronic pruritus, and address clinical considerations. Results: Preclinical studies have found neural pathways underlying detection, transmission, and modulation of itch signaling and spotlighted the importance of neuronal KOR and MOR in itch perception. Clinical reports suggest that opioid axis modulation may be the basis for the successful treatment of chronic itch. Several agents (MOR antagonist naltrexone; KOR agonists nalfurafine and difelikefalin; dual-acting KOR agonists/MOR antagonists butorphanol and nalbuphine) have been evaluated for treating chronic pruritus in case series, small studies, and clinical trials; nalbuphine has progressed through preliminary (phase II/III) studies in uremic pruritus and prurigo nodularis. The antipruritic efficacy of these agents has been observed across multiple disorders with disparate etiologies, suggesting the potential utility of this class to provide a unified approach to chronic pruritus treatment. Conclusions: The relative safety of these agents, including a reduced potential for dependence versus MOR-agonist analgesics, should help overcome resistance to the use of opioid receptor-targeting agents in chronic pruritus treatment.